The role of volunteers in the radiology department of wuhan leishenshan hospital: A mini review from a single study center - Hu, Jinxiang; Deng, Ming (Archives of Community Medicine and Public Health, 2020)
This retrospective report, detailed the volunteer work of the radiology department in Wuhan Leishenshan Hospital at the COVID-19 epidemic period. Under the background of the lack of medical staff, we pointed out that the special hospital is not restricted in one pattern, and, which has laid a solid foundation for the effective development of the medical treatment. During the past two months, the volunteers showed strong humanistic care and selfless dedication, which provided manpower guarantee for spreading positive energy and conquering the COVID-19 epidemic as soon as possible. Such a program could serve as a model for common reference throughout the world. The author summarizes the report and pay tribute to the volunteers from all over the world.